IDENTIFIKASI SPESIES LALAT BUAH DENGAN MEDIA BUAH PEPAYA DAN BUAH MANGGA DI KENALI ASAM, JAMBI - Zahra, Mahar Hazzillia Az; Rohman, Nur; Salsabila, Syifa; Salsabila, Niken Alya; Hamidah, Afreni; Tentia, Ine; Saparuddin, Saparuddin; Siburian, Jodion (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2025)
Background: This research was conducted with the aim of observing and obtaining information about fruit fly species in the home area of Kenali Asam, Jambi. Methods: Research was carried out using experimental methods and a microscope. The trapping medium uses mango and papaya that have been left to rot. Put the two types of fruit in a container and wait for the fruit flies to get inside. Results: The results of the study show that there is diversity in fruit fly species in the home area of Kenali Asam, Jambi. Conclusion: This research emphasizes the importance of understanding how to make fruit fly stock media (rejuvenation media) that is appropriate and remains hygienic. This research also requires further studies to explore factors that can influence the development of fruit flies and their distribution in various environments